2021
DOI: 10.21926/aeer.2102012
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Organic Pollutants in Urban Soils of Central of London, England, UK: Measurement and Spatial Modelling of Black Carbon (BC), Petroleum Hydrocarbons (TPH), Polycyclic Aromatic Hydrocarbons (PAH) and Polychlorinated Biphenyls (PCB)

Abstract: Total organic carbon (TOC), black carbon (BC), total petroleum hydrocarbons (TPH), polycyclic aromatic hydrocarbons (PAH) and polychlorinated biphenyls (PCB) were determined in 73 surface (0-2 cm) and subsurface (5-20 cm) soil samples taken from a 142 km2 area in Central London, UK. Soils were assessed to provide a baseline chemistry for site owners, developers, occupiers and regulators involved in understanding the potential risk to human health and the environment. TOC range was 1.75-11.85 % (mean 5.82 %), B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 94 publications
(176 reference statements)
0
3
0
Order By: Relevance
“…For deposits within the EA/NRW databases which contained wastes of multiple origin, these were recategorised as "mixed" wastes. Within these mixed wastes, a further category was generated based on landfill closure date to categorise those which were more likely to contain wastes from the 1960s-70s, which are reported to contain hazardous organic contaminants whose production has since been legislated against, such as poly-chlorinated biphenyls (PCBs: Harrad et al, 1994) and persistent organic pollutants (POPs: Vane et al, 2021). As a result of this process, 10 waste categories were generated, which were then straight-ranked (high to low; 1.0 to 0.1) based on their perceived relative likelihood of containing hazardous priority substances, and their potential leaching products (based on authors' consensus and literature review), as detailed in Table 1.…”
Section: Waste Type (Source)mentioning
confidence: 99%
“…For deposits within the EA/NRW databases which contained wastes of multiple origin, these were recategorised as "mixed" wastes. Within these mixed wastes, a further category was generated based on landfill closure date to categorise those which were more likely to contain wastes from the 1960s-70s, which are reported to contain hazardous organic contaminants whose production has since been legislated against, such as poly-chlorinated biphenyls (PCBs: Harrad et al, 1994) and persistent organic pollutants (POPs: Vane et al, 2021). As a result of this process, 10 waste categories were generated, which were then straight-ranked (high to low; 1.0 to 0.1) based on their perceived relative likelihood of containing hazardous priority substances, and their potential leaching products (based on authors' consensus and literature review), as detailed in Table 1.…”
Section: Waste Type (Source)mentioning
confidence: 99%
“…Each tree is grown on a random subsample of the training data and a random subset of the predictor variables to choose from at each decision node. In this study, we used the RF modelling approach suggested by Cave [27], in which inverse distance weighted (IDW) covariates are used as the predictor variables and subsequently used to predict the spatial distribution of persistent organic pollutants in London [28]. Inverse distance weighted (IDW) interpolation explicitly makes the assumption that samples that are close to one another are more alike than those that are further apart [29].…”
Section: Spatial Modellingmentioning
confidence: 99%
“…Similarly to kriging, the RF methods can also produce prediction variance estimates derived from the bootstrap sampling of the data points (inherent in the RF algorithm). This approach has subsequently been used to predict the spatial distribution of persistent organic pollutants in London (Vane et al, 2021), and produce spatial prediction models of the total and bioaccessible fractions of arsenic and lead in an urban environment (Wragg and Cave, 2021).…”
Section: Introductionmentioning
confidence: 99%